Educational homogamy in Norway: Trends and patterns - Gunn Elisabeth Birkelund; Johan Heldal (University of Oslo, Department of Economics, 2000)
This paper focuses on trends and patterns in educational homogamy over time. A number of previous studies have documented a fairly high level of homogamy in Norway. Most of these studies, however, have been local and ethnographic, or based on national data measuring homogamy within a limited time period. Based on a 10 percent sample of the 1980 Census, we are comparing patterns of educational homogamy across six cohorts, where the oldest is born between 1900-1909. The results show a decline in educational homogamy over time, both in absolute terms and when controlling for the general increase in educational level during the period.
Keywords: 330; Educational homogamy; log-linear models; time trends; Bildungsniveau; Familiensoziologie; Norwegen; Ehe